2021
DOI: 10.3390/d13100490
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Density, Population Size and Distribution of the Endangered Western Hoolock Gibbon (Hoolock hoolock) in Forest Remnants in Bangladesh

Abstract: Tropical forests are threatened worldwide due to deforestation. In South and Southeast Asia, gibbons (Hylobatidae) are important to seed dispersal and forest regeneration. Most gibbons are threatened due to deforestation. We studied the western hoolock gibbon (Hoolock hoolock) in Bangladesh to determine population size and extent of suitable habitat. We used distance sampling to estimate density across 22 sites in northeastern and southeastern Bangladesh. We used Maxent modeling to determine areas of highly su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The Western hoolock gibbon and Assamese macaque entirely inhabit the trans-boundary forest areas with less human disturbance whilst the remaining primate fauna were found mostly in the plantation forests across the boundary. Naher et al (2021) reported three groups of Western hoolock gibbon from the PHR whilst the Bengal slow was detected by a recent study (Choudhury et al 2022). The Rhesus macaque was common across the plantation forests, with frequent sightings on south and western regions.…”
Section: Resultsmentioning
confidence: 92%
“…The Western hoolock gibbon and Assamese macaque entirely inhabit the trans-boundary forest areas with less human disturbance whilst the remaining primate fauna were found mostly in the plantation forests across the boundary. Naher et al (2021) reported three groups of Western hoolock gibbon from the PHR whilst the Bengal slow was detected by a recent study (Choudhury et al 2022). The Rhesus macaque was common across the plantation forests, with frequent sightings on south and western regions.…”
Section: Resultsmentioning
confidence: 92%
“…At noon, the macaque traveled more to find suitable areas with high food abundance where the group would remain safe until sunset. During the afternoon, group members spent more time for foraging and feeding in preparation to stay healthy for the whole night (Khan, 2020 andAkhter, 2021).…”
Section: Diurnal Variation Of Different Activitiesmentioning
confidence: 99%